Diabetes mellitus and the skin - Adriana Lucia Mendes; Helio Amante Miot; Vidal Haddad Junior (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Several dermatoses are routinely associated with diabetes mellitus, especially in patients with chronic disease. This relationship can be easily proven in some skin disorders, but it is not so clear in others. Dermatoses such necrobiosis lipoidica, granuloma annulare, acanthosis nigricans and others are discussed in this text, with an emphasis on proven link with the diabetes or not, disease identification and treatment strategy used to control those dermatoses and diabetes.